2019
DOI: 10.5539/gjhs.v11n5p1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Towards Energy Drinks Consumption and Related Factors Among Young Male Athletes in the United Arab Emirates

Abstract: OBJECTIVES: We aim to investigate the knowledge towards Energy Drinks (EDs) consumption and related factors among young male athletes in the United Arab Emirates (UAE). SUBJECTS & METHODS: A cross-sectional study included 688 young male athletes from Al Ain sports club aged between 7 to 18 years. Data were collected using a modified version of a validated questionnaire from the European Food Safety Authority. RESULTS: Overall EDs consumption was 24%. About 44% of the athletes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…33 In our previous study, we assessed ED consumption among young athletes in Al Ain city (between May and October 2017) before implementing 100% tax on ED and found that the overall ED consumption was 24% among 688 male participants aged between 7 and 18 years. 23 Comparing with this study, which was conducted after the tax implementation, the consumption rate is 27% among 1611 participants aged between 10 and 18 years. Our results suggest that despite the tax implementation, ED consumption remains popular among young people.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…33 In our previous study, we assessed ED consumption among young athletes in Al Ain city (between May and October 2017) before implementing 100% tax on ED and found that the overall ED consumption was 24% among 688 male participants aged between 7 and 18 years. 23 Comparing with this study, which was conducted after the tax implementation, the consumption rate is 27% among 1611 participants aged between 10 and 18 years. Our results suggest that despite the tax implementation, ED consumption remains popular among young people.…”
Section: Discussionmentioning
confidence: 76%
“…8 This could be explained as older adolescents are more exposed to ED marketing and have easier access to it. Recent studies found that even children are consuming EDs 22,23 ; this is a cause of concern as regular consumption of these beverages containing caffeine, sugar, and other stimulant ingredients showed to be related to other adverse health effects. [8][9][10]24 Moreover, we found a relationship between ED consumption and parents' educational level.…”
Section: Discussionmentioning
confidence: 99%
“…Another major problem that affects child health in the UAE is the increasing consumption of energy drinks among children (notably cited in Almulla & Faris, 2020;Bhojaraja et al, 2016;Ghozayel et al, 2020;Almulla & Zoubeidi, 2022;Almulla et al, 2019). According to Kharaba et al (2022), 16.3% of the children consumed energy drinks.…”
Section: Why Child Health Is a Concern In Uae?mentioning
confidence: 99%